Current process in hearing-aid fitting appointments: An analysis of audiologists' use of behaviour change techniques using the behaviour change technique taxonomy (v1) - Barker, F; Mackenzie, E; De Lusignan, S (Taylor and Francis, 2016)
To observe and analyse the range and nature of behaviour change techniques (BCTs) employed by audiologists during hearing-aid fitting consultations to encourage and enable hearing-aid use.Non-participant observation and qualitative thematic analysis using the behaviour change technique taxonomy (version 1) (BCTTv1).Ten consultations across five English NHS audiology departments.Audiologists engage in behaviours to ensure the hearing-aid is fitted to prescription and is comfortable to wear. They provide information, equipment, and training in how to use a hearing-aid including changing batteries, cleaning, and maintenance. There is scope for audiologists to use additional BCTs: collaborating with patients to develop a behavioural plan for hearing-aid use that includes goal-setting, action-planning and problem-solving; involving significant others; providing information on the benefits of hearing-aid use or the consequences of non-use and giving advice about using prompts/cues for hearing-aid use.This observational study of audiologist behaviour in hearing-aid fitting consultations has identified opportunities to use additional behaviour change techniques that might encourage hearing-aid use. This information defines potential intervention targets for further research with the aim of improving hearing-aid use amongst adults with acquired hearing loss.